Effect of a Flaxseed Lignan Intervention on Circulating Bile Acids in a Randomized, Crossover Trial. (29th May 2020) - Navarro, Sandi; Levy, Lisa; Randolph, Timothy; Hong, Natalie; Neto, Fausto; Raftery, Daniel; Chapkin, Robert; Lampe, Johanna; Hullar, Meredith
Abstract: Objectives: Health benefits of high-fiber foods may be attributed, in part, to microbial metabolites of plant compounds. Lignans and their microbial metabolites, the enterolignans [enterolactone (ENL) and enterodiol (END)], reduce serum lipids through a variety of mechanisms, including regulation of bile acid (BA) synthesis. BA, released into the gut lumen in response to dietary fat, undergo microbial metabolism to secondary (2°) BA, which have been positively associated with chronic disease, e.g., liver disease and colorectal cancer. Our aims were to evaluate the effects of a flaxseed lignan supplement on circulating BA and examine associations between enterolignans and 2° BA. Methods: We conducted a randomized, crossover trial of a flaxseed lignan supplement (50 mg/d secoisolariciresinol diglucoside) compared to placebo in 46 healthy men and women (20-45 y). Each period lasted 60 days, separated by a 60-day washout period. Six primary and fourteen 2° BA species were measured in fasting plasma using LC-MS. ENL and END were measured in 24-h urines by GC-MS. Low- and high-ENL excreters were defined as below and above the median 24-h ENL excretion at the end of the flaxseed lignan intervention (23.4 µmol/24 h). Linear mixed models were used to a) test the effects of the intervention on individual BA concentrations, overall and stratified by low and high ENL excreters; and b) to cross-sectionally determine the association between plasma 2 o BA and ENL and END. Results: There was no significant effect of the flaxseed lignan intervention compared to placebo on BA concentrations overall, or by ENL-excreter status, after FDR adjustment. In the cross-sectional analysis, irrespective of treatment, six 2° BA were statistically significantly associated with ENL (FDR < 0.05), with two positive associations (isolithocholic and lithocholic acids), and four inverse associations (glycoursodeoxycholic, glycohyodeoxycholic, hyodeoxycholic, and muricholic acids). Conclusions: The flaxseed lignan intervention and subsequent ENL production had no effect on plasma BA concentrations. However, the strong associations between ENL excretion and certain 2° BA concentrations suggests that the gut microbial communities capable of producing ENL may also play a role in 2° BA metabolism. Funding Sources: NIH.